DETERMINAN INDIKATOR MAKRO EKONOMI TERHADAP REKSA DANA SYARIAH DI INDONESIA PERIODE 2014-2021 - Nur Azifah; Stevani Adinda Nurul Huda; Siti Aisyah (Asosiasi Dosen Muda Indonesia, 2022)
This research aims to determine how macroeconomic indicators affect the net asset value of Islamic mutual funds in Indonesia from January 2014 to December 2021. This study employs the Linear Ordinary Least Squares (OLS) regression method with a saturated sample approach (census), with inflation, exchange rate, Bank Indonesia Syariah Certificate (SBIS), BI Rate 7 days repo, and money supply as independent variables and net asset value of sharia mutual funds as the dependent variable. According to the study's findings, inflation, exchange rate, SBIS, BI Rate, and JUB all significantly influence the net asset value (NAV) of Islamic mutual funds in Indonesia. These findings imply that macroeconomic indicators play an essential role in expanding the Islamic capital market sector in Indonesia, particularly sharia mutual funds, and that monetary stability in the domestic economy will affect the increase in people who invest their funds in sharia mutual funds instruments.